CHALLENGES FACED BY RURAL STUDENTS IN LEARNING ENGLISH - Khudoyorova Gulasal Ihomiddinovna. (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study explores the challenges faced by rural students in learning English, with a particular focus on the educational context of Uzbekistan. Despite the growing importance of English as a global language and its role in securing scholarships, employment, and international mobility, rural learners continue to face significant barriers to effective learning. Using a combination of classroom observations, personal teaching experience, and informal interviews with rural students, the research identifies key obstacles such as limited access to qualified teachers, outdated learning materials, inadequate exposure to real-life English use, and socio-economic constraints. In addition, cultural perceptions and traditional mindsets often discourage students, particularly girls, from fully investing in English education.The findings call for targeted policy measures, improved teacher training, digital access, and community support programs to bridge the rural-urban gap.